HUBUNGAN ANTARA JENIS BATU DAN PERUBAHAN MUKOSA KANDUNG EMPEDU PADA PASIEN BATU KANDUNG EMPEDU - Kereh, David S.; Lampus, Harsali; Sapan, Hebert B.; Loho, Lily L. (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: This study aimed to analyze the relationship between gallstone and histopathological changes of gallbladder mucosa among patients with gallstones. Samples consisted of 38 patients with gallstones who were performed elective cholecystectomy either by laparoscopy or by laparotomy on them. Gallstones were analyzed macroscopically to determine the types of stones. Specimens of resected gallbladders were examined histopathologically to obtain the changes of gallbladder mucosa. The results showed that macroscopical analysis resulted in three types of gallstones: cholesterol stone (76.3%), pigmented stone (21.1%), and mixed stone 2.6%). Histopathologically, all resected speciments showed changes of gallbladder mucosa in the forms of chronic inflammation or associated with hyperplasia. There was no incidental cases of gallbladder cancer. An analysis of the relationship between the types of stones and the histopathological changes of gallbladder mucosa with the chi-square test showed an X2 value of 0.483 and a P value of 0.392. Conclusion: In this study, there was no relationship between the types of gallstones and the histopathological changes of gallbladder mucosa among patients with gallstone.Keywords: gallstone, cholecystectomy, gallbladder mucosaAbstrak: Penelitian ini bertujuan untuk menganalisis hubungan batu kandung empedu dengan perubahan mukosa kandung empedu pada pasien dengan batu kandung empedu. Sampel terdiri dari 38 pasien batu kandung empedu yang menjalani operasi elektif kolesistektomi, baik secara laparoskopik maupun secara terbuka. Batu kandung empedu dianalisis secara makroskopik untuk menentukan jenis batu. Spesimen reseksi kandung empedu diperiksa secara histopatologik untuk melihat ada tidaknya perubahan mukosa kandung empedu. Dari hasil analisis batu secara makroskopik didapatkan 3 jenis batu kandung empedu, yaitu batu kolesterol (76,3%), batu pigmen (21,1%), dan batu campuran (2,6%). Semua spesimen reseksi kandung empedu diperiksa secara histopatologik dan menunjukkan perubahan mukosa kandung empedu berupa radang kronis dan hiperplasia. Tidak terdapat penemuan secara insidental terhadap kanker kandung empedu. Analisis hubungan antara jenis batu kandung empedu dan perubahan mukosa kandung empedu dengan uji chi-square mendapatkan X2 = 0,483 dengan P = 0,392. Simpulan: Dalam penelitian ini tidak didapatkan hubungan antara jenis batu dan perubahan mukosa kandung empedu pada pasien dengan batu kandung empedu.Kata kunci: batu kandung empedu, kolesistektomi, mukosa kandung empedu